2020
DOI: 10.12913/22998624/116971
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostics of Transient States in Hydraulic Pump System with Short Time Fourier Transform

Abstract: In hydraulic pump system various states can occur caused by mechanical and physical phenomena. To detect them, the Short Time Fourier Transform (STFT) is applied. This paper will consider an application of STFT to monitor and evaluate hydraulic pump system operation in different states of operation. For measurements of pressure and flow changes in pump, hydraulic tester and Data AcQuisition (DAQ) card was used for evaluation of qualitative and quantitative changes in the system. Results of hydraulic pump's ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…Nowadays, the MFO algorithm is deeply studied to solve multi-objective problems, unconstrained optimization problems, global optimization problems, and so on [13][14][15][16][17][18]. The MFO algorithm has been proved to be effective in networks [19,20], manufacturing [21], power systems [22][23][24], control [25], energy [26][27][28], reliability analysis [29][30][31], autonomous robot navigation [32], testing [33], photovoltaic modules [34], biomedical science [35][36][37], and so on. The MFO algorithm can then be utilized to optimize and improve the accuracy of the classification algorithm for the purpose of network intrusion detection.…”
Section: Related Workmentioning
confidence: 99%
“…Nowadays, the MFO algorithm is deeply studied to solve multi-objective problems, unconstrained optimization problems, global optimization problems, and so on [13][14][15][16][17][18]. The MFO algorithm has been proved to be effective in networks [19,20], manufacturing [21], power systems [22][23][24], control [25], energy [26][27][28], reliability analysis [29][30][31], autonomous robot navigation [32], testing [33], photovoltaic modules [34], biomedical science [35][36][37], and so on. The MFO algorithm can then be utilized to optimize and improve the accuracy of the classification algorithm for the purpose of network intrusion detection.…”
Section: Related Workmentioning
confidence: 99%
“…These researchers in their proposal only work with SNR ≥ 0 dB. For their part, the authors in [8] created an algorithm using the short-time Fourier transform for the diagnosis of transient states in a hydraulic pump system. In the results presented by these researchers, it is observed that when noise begins to increase, there is deterioration in the extraction of characteristics of the studied signal.…”
Section: Introductionmentioning
confidence: 99%
“…The contamination of gear oils with wear products may result in power losses, among other consequences, as well as decreases in the flow resistance of the lubricant [19]. Therefore, the quality and condition of the lubricant affects the friction resistance in gear boxes and may affect the efficiency of tribomechanical systems [20,21]. The applications that oil is used for may lead to changes in its viscosity [19].…”
Section: Introductionmentioning
confidence: 99%